UMP won i-ENVEX 2018 Special Award - Nur Laila, Afandi (2018)
Perlis, 15 April – Students of Universiti Malaysia Pahang (UMP) has won the Special Award, Double Gold, 5 gold and 1 bronze medal at the International Engineering Invention & Innovation Exhibition (iVEVE) 2018 competition organized by Universiti Malaysia Perlis (UniMAP).